The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1073/pnas.88.11.4708
|View full text |Cite
|
Sign up to set email alerts
|

Targeted inactivation of the insulin receptor gene in mouse 3T3-L1 fibroblasts via homologous recombination.

Abstract: To study the role of the insulin receptor in determining adipocyte differentiation of the mouse cell line 3T3-L1, we have introduced a mutation that inactivates the insulin receptor gene by homologous recombination. In two independent clones, inactivation of one allele of the insulin receptor gene was associated with a 50-70% reduction in the number, of insulin receptors. In addition, both clones were markedly impaired in their ability to differentiate into adipocytes. The defect in adipocyte-specific differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 35 publications
8
36
0
Order By: Relevance
“…High concentrations of insulin (1 M) are thought to induce differentiation of 3T3-L1 preadipocytes through activation of the IGF I receptor (36). However, gene targeting of one insulin receptor allele in 3T3-L1 preadipocytes impaired the ability of these cells to differentiate into adipocytes (37), suggesting that insulin can play a direct role in the differentiation of the 3T3-L1 cells. The present studies support the notion that the insulin receptor cytoplasmic domain is also capable of initiating the intracellular signals sufficient for adipocyte differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…High concentrations of insulin (1 M) are thought to induce differentiation of 3T3-L1 preadipocytes through activation of the IGF I receptor (36). However, gene targeting of one insulin receptor allele in 3T3-L1 preadipocytes impaired the ability of these cells to differentiate into adipocytes (37), suggesting that insulin can play a direct role in the differentiation of the 3T3-L1 cells. The present studies support the notion that the insulin receptor cytoplasmic domain is also capable of initiating the intracellular signals sufficient for adipocyte differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…In this respect it is interesting to note that IGF-1 can exert hypoglycaemic, but not lipogenic effects, in IR ±/± mice [27]. In a different model, we have previously shown that partial inactivation of the IR gene in 3T3-L1 cells is associated with impaired adipocyte differentiation, and that this defect can be reversed by over-expression of IRs [28]. Interestingly, not all dermal areas are equally susceptible to insulin resistance; for example, the decrease of fat content in abdominal and thoracic areas is more marked than in dorsal areas.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be speculated that FoxOs may have some important roles in these tissues. Insulin or other growth factors are important for adipocyte differentiation [89][90][91][92]. However, it has not been known about the mechanism how these growth factors can regulate adipocyte differentiation.…”
Section: Adipose Tissuesmentioning
confidence: 99%